2016
DOI: 10.3390/toxins8110316
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic Effect of Piperine in Broiler Chickens Intoxicated with Aflatoxin B1

Abstract: Piperine is an abundant amide extracted from black pepper seeds which has been shown to have protective effects against cytotoxic and genotoxic carcinogenesis induced by certain chemical carcinogens and aflatoxin B1 (AFB1) in vitro. The aim of this work was to study, in vivo, the antigenotoxic potential of feed-added piperine on broiler chickens experimentally intoxicated with AFB1, using micronucleus and comet assays. The antigenotoxicity assessment of 9-day-old chicks was performed on a total of 60 chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…For more, piperine decreases the cytotoxicity and genotoxicity of aflatoxin B1, through inhibition of metabolization pathways shown in vitro ( 39 ). In broiler chickens intoxicated by AFB1 (ingestion of 0.5 mg AFB1 kg −1 bw); piperine (60 mg kg −1 ) was able to reduce or even prevent the genotoxic and cytotoxic effects, presenting a safe option for the protection and supportive treatment of aflatoxicosis ( 40 ).…”
Section: Selected Herbal Bioenhancersmentioning
confidence: 99%
“…For more, piperine decreases the cytotoxicity and genotoxicity of aflatoxin B1, through inhibition of metabolization pathways shown in vitro ( 39 ). In broiler chickens intoxicated by AFB1 (ingestion of 0.5 mg AFB1 kg −1 bw); piperine (60 mg kg −1 ) was able to reduce or even prevent the genotoxic and cytotoxic effects, presenting a safe option for the protection and supportive treatment of aflatoxicosis ( 40 ).…”
Section: Selected Herbal Bioenhancersmentioning
confidence: 99%
“…c c e p t e d M a n u s c r i p tThe beneficial potential of certain chemicals (β-glucans, equol, vitamin E) and specially developed feed additives that protect animal health as well as deficiency of certain micronutrients and effects of feed restrictions was also assessed. Results showed protective properties against DNA damaging effects of mycotoxins and hydrogen peroxide or the type of diet used during the production indicating a genoprotective effects, in addition to the DNA damaging effects of certain stressors[291][292][293]297,299,[301][302][303][304].…”
mentioning
confidence: 99%
“…Moreover, PIP has been proposed as an alternative growth promoter to antibiotics in animal diets [9,25]. However, while its beneficiary effects in poultry has been investigated [25][26][27][28], its impact on porcine health remains relatively elusive. In previous study, we have previously demonstrated that expression of EPO and EPO-R is upregulated by GABA and PIP in combination in epithelial kidney cell lines through MAPK pathway [11].…”
Section: Discussionmentioning
confidence: 99%